Prevalence of Dyslipidemia Among Antiretroviral-Naive HIV-Infected Individuals in China. Issue 48 (December 2015) - Shen, Yinzhong; Wang, Jiangrong; Wang, Zhenyan; Qi, Tangkai; Song, Wei; Tang, Yang; Liu, Li; Zhang, Renfang; Lu, Hongzhou
Abstract : Abstract: Little is known about the epidemiological features of dyslipidemia among antiretroviral-naive HIV-infected individuals in China. We used a cross-sectional study design to estimate the prevalence of dyslipidemia in this population, and to identify risk factors associated with the presence of dyslipidemia. One thousand five hundred and eighteen antiretroviral-naive HIV-infected individuals and 347 HIV-negative subjects in China were enrolled during 2009 to 2010. Demographics and medical histories were recorded. After an overnight fast, serum samples were collected to measure lipid levels. Factors associated with the presence of dyslipidemia were analyzed by logistic regression. Mean total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL) levels were lower in HIV-positive than HIV-negative subjects, but mean triglyceride (TG) was higher in HIV-positive subjects. The overall prevalence of dyslipidemia in HIV-positive and HIV-negative groups did not differ (75.6% vs. 73.7%, P = 0.580). However, the prevalence of high TC (8.4% vs. 28.2%, P < 0.001) and high LDL (8.5% vs. 62.6%, P < 0.001) was lower in HIV-positive than HIV-negative subjects, and the prevalence of high TG (33.9% vs. 17.0%, P < 0.001) and low HDL (59.6% vs. 11.2%, P < 0.001) was higher in HIV-positive than HIV-negative subjects. Logistic analysis showed that HIV positivity was significantly associated with both an increased risk of high TG and low HDL and a decreased risk of high TC and high LDL. The mean levels of TC, of LDL and of HDL showed an increasing trend with increasing CD4 count in HIV-positive subjects. Multivariable logistic regression found that lower CD4 count was significantly associated with both an increased risk of high TG and low HDL and a decreased risk of high TC in HIV-positive subjects. Among antiretroviral-naive HIV-infected Chinese adults, there was a high prevalence of dyslipidemia characterized by high TG and low HDL, which was associated with lower CD4 counts. These data support the assessment of lipid profiles before and after initiation of antiretroviral therapy regardless of age.